Antiarrhythmic effect of ranolazine in combination with selective NCX-inhibition in an experimental model of atrial fibrillation. (25th November 2020) - Wolfes, J; Ellermann, C; Broer, N; Willy, K; Rath, B; Leitz, P; Wasmer, K; Eckardt, L; Frommeyer, G
Abstract: Background: Previous studies showed an antiarrhythmic effect of ranolazine in different clinical and experimental studies. The aim of this study was to investigate the effects of a combination of ranolazine with different selective NCX-inhibitors in an established experimental model of atrial fibrillation. Methods and results: 18 hearts of New Zealand white rabbits were retrogradely perfused. Left and right atrial catheters were used to record monophasic action potentials. Hearts were paced at three different cycle lengths (350ms, 250ms, 150ms). Thereby, cycle-length dependent atrial action potential durations (aAPD90), atrial effective refractory periods (aERP) and atrial post-repolarization refractoriness (aPRR=aERP-aAPD90) were obtained. Vulnerability to AF was tested by a standardized protocol employing several trains of burst pacing. After generating baseline data, the hearts were perfused with a combination of acetylcholine (ACh, 1μM) and isoproterenol (Iso, 1μM) to increase occurrence of AF. Afterwards, the hearts were assigned to two groups and additionally perfused with a combination of 10 μM ranolazine and 1 μM of the selective NCX-inhibitor ORM-10103 (group 1: Rano-ORM) or 10 μM ranolazine and 1 μM of another NCX-inhibitor, SEA0400 (group 2: Rano-SEA). Infusion of ACh/Iso led to a shortening of aAPD90 (group 1/2: −27.2ms/−24.5ms p<0.05), aERP (−29.2ms/−35.6ms p<0.05), aPRR (−12.2ms/−13.7ms p=ns) and the occurrence of AF-Episodes was significantly increased (group 1: baseline 6 episodes to 34 episodes under ACh/Iso p<0.05, group 2: baseline 7 episodes to 26 episodes under ACh/Iso p<0.05). Additional perfusion with ranolazine and ORM-10103 did not alter aAPD90 (−0, 47ms) while effective refractory periods (+21.4ms, p<0.05) and aPRR (+43ms, p<0.05) were significantly prolonged and AF episodes were effectively reduced to 15 episodes (p<0.05). In group 2, Rano-SEA led to a slight decrease in aAPD90 (−9.5ms) while aERP (+13.3ms, p<0.05) and aPRR (+19.8ms, p<0.05) were prolonged. The occurrence of AF episodes was reduced to 15 episodes (p=0.1). Conclusion: To our knowledge this is the first study investigating the effect of ranolazine combined with different selective NCX-inhibitors in an isolated whole-heart model of AF. Atrial repolarization was not significantly changed with either of the combinations. However, both combinations prolonged aERP and aPRR and thereby suppressed induction of AF. Combining novel cellular targets may therefore lead to new potentially interesting options for antiarrhythmic AF therapy that have to be tested in clinical studies. Funding Acknowledgement: Type of funding source: None